2008
DOI: 10.19030/tlc.v5i7.1244
|View full text |Cite
|
Sign up to set email alerts
|

Student Grade Motivation As A Determinant Of Performance On The Business Major Field ETS Exam

Abstract: This paper examines the determinants of performance on the business major field achievement ETS exam with a focus on the impact of applying ETS exam scores to part of the capstone course grade as a performance incentive.  The sample consists of 150 students at a midsized regional institution located in the Southwestern region of the United States.  The empirical model employed controls for grade point average, standardized test scores (SAT/ACT), junior college transfer students, and gender.  The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…This pattern has been shown in a number of other investigations (Sundre, ; Sundre & Kitsantas, ; Terry, Mills, & Sollosy, ; Wolf & Smith, ; Wolf, Smith, & DiPaolo, ). For example, other studies have shown that taking a test that has consequences for course placement, promotion, graduation, or admission influences test performance via motivation (Cole & Osterlind, ; DeMars, ; Liu et al, ; Rothe, ).…”
Section: Test Conditions Shown To Influence Motivationsupporting
confidence: 79%
“…This pattern has been shown in a number of other investigations (Sundre, ; Sundre & Kitsantas, ; Terry, Mills, & Sollosy, ; Wolf & Smith, ; Wolf, Smith, & DiPaolo, ). For example, other studies have shown that taking a test that has consequences for course placement, promotion, graduation, or admission influences test performance via motivation (Cole & Osterlind, ; DeMars, ; Liu et al, ; Rothe, ).…”
Section: Test Conditions Shown To Influence Motivationsupporting
confidence: 79%
“…SAT scores have been shown to be associated with higher grades from high school through college (Bernardi & Bean, 1999;Bernardi & Kelting, 1997) as well as higher scores on the certified public accountant (CPA) examination (National Association of State Boards of Accountancy [NASBA], 1994). All previous research on MFT-B has found ACT and SAT scores to be positively and significantly correlated with MFT-B scores (Allen & Bycio, 1997;Bagamery, Lasik, & Nixon, 2005;Bean & Bernardi, 2002;Bielinska-Kwapisz, Brown, & Semenik, 2012;Black & Duhon, 2003;Bycio & Allen, 2007;Mirchandani, Lynch, & Hamilton, 2001;Terry, Mills, & Sollosy, 2008). Therefore, we expect general intellectual ability (as measured by ACT) to have a positive impact on performance on the MFT-B.…”
Section: Actmentioning
confidence: 78%
“…Because the MFT-B's goal is to test general business knowledge, GPA should be the most important predictor of the MFT-B performance. All previous studies have found GPA to be a significant determinant of performance on the MFT-B (Allen & Bycio, 1997;Bielinska-Kwapisz, et al, 2010;Black & Duhon, 2003;Bycio & Allen, 2007;Mirchandani, et al, 2001;Terry et al, 2008). Rook and Tanyel (2009) found that business core GPA was a slightly better predictor of test improvement than upper level business GPA.…”
Section: Gpamentioning
confidence: 93%
See 2 more Smart Citations